Mutation Technique for Increasing the Production of Antibacteria Lactobacillus plantarum TGR-2 - Sebastian Margino; Sri Winarti; Retno Indrati; Endang S. Rahayu (Indonesian Association of Food Technologists, 1998)
Production of antibacteria of Lactobacillus plantarum TGR-2 was carried out by mutation technique using UV radiation and chemical mutagenic agent (acrydine orange (AO), ethyl methane sulfonate (EMS), and N-methyl-N-nitro sulfonate nitrosoguanidine (NTG). As a marker was applied chloramphenicol for 10 ppm. Total 214 mutants were obtained from all of the treatments and then screened based on their activities against Staphylococcus aureus FNCC 0047 as bacterial indicator, using agar diffusion and turbidimetric assay techniques. Results showed that 24 mutants could produce higher amount of antibacteria and two of them, NTG and acrydine orange treatments, had higher stability than others. Characterization of two mutants, determination of biochemistry traits and optimization of antibacterial (bacteriocin) production were done. The product showed that UV-15, EMS-10, AO-6 and NTG-21 mutants could produce antibacterial substance 3,90, 4.40, 3.40 and 4.17 AU/ml for 16, 12, 12, and 16 hours incubation, respectively, compared to Lactobacillus plantarum TGR-2 which produced 1.07 UA/ ml for 24 hours incubation.